What Makes or Breaks Evidence-Based Supervision? Staff and Organizational Predictors of Evidence-Based Practice in Probation. (May 2023) - Debus-Sherrill, Sara; Breno, Alex; Taxman, Faye S.
Research on staff and organizational factors that affect receptivity, adoption, feasibility, and utilization of innovations in justice settings is limited. This study uses survey data from 349 employees in one probation agency to assess how staff and perceived organizational factors influence attitudes related to evidence-based practices (EBPs) and their self-reported use. Staff characteristics, including education and knowledge about EBPs, and perceptions of the organization, including cynicism about the organization's ability to change, predicted EBP outcomes. Staff age, tenure at the agency, and caseload size affected perceptions of organizational culture, but did not predict attitudes or use of EBPs. There is weak evidence for a relationship between self-reported use of EBPs with attitudinal support for EBPs, prior EBP training, and knowledge of EBPs. This study contributes to an emerging body of literature about the impact of various individual and organizational factors on support for EBPs with important lessons for implementation.